Adjustment disorder and risk of Parkinson's disease. (12th January 2016) - Svensson, E.; Farkas, D. K.; Gradus, J. L.; Lash, T. L.; Sørensen, H. T.
Abstract : Background and purpose: It has been postulated that stress is part of the etiological process of Parkinson's disease (PD). The risk of PD was examined in a cohort of patients with adjustment disorders, a diagnosis made in the presence of a severe response to a stressful life event. Methods: Using Danish medical registries, PD occurrence was examined in a nationwide population‐based cohort of patients with adjustment disorder diagnosed between 1995 and 2011. The standardized incidence ratio of PD was calculated as the ratio of observed to expected cases, stratified by time and potential risk factors, including depression and anxiety. Results: Our adjustment disorder cohort (67 786 patients) was followed for a median of 8 years (interquartile range 4, 12.6 years). During follow‐up, 119 patients developed PD, versus 64 expected, corresponding to a standardized incidence ratio of 1.84 (95% confidence interval 1.53, 2.20). Consistent results were observed after stratification on potential risk factors, including depression and anxiety. Conclusion: Adjustment disorder, a diagnosis made in the presence of severe response to stressful life events, was associated with an increased risk of PD.